Analysis of transversal competences in the professional training of Administration and Finance from the perspective of employability in Spain - Nieto Ortiz, Jorge (Avances en Supervisión Educativa, 2020)
Administration and Finance is a higher level training cycle that covers the organization and execution of management and administration operations in commercial, labour, accounting, tax and financial processes, from a marked multidisciplinary and transversal nature. In addition to technical knowledge, other transversal competences to different sectors of activity or functions within the company, such as responsibility, autonomy, proactivity, teamwork, customer orientation, etc. are important. The acquisition of transversal competencies encourages the employability of students because they cover different jobs, regardless of the functions performed in the company, sector of activity in which it operates or, even the size of the company. The study is a documentary analysis of publications related to the prospective of the degree in order to detect those training needs in transversal competences demanded in their professional environment and, the approach of new training actions in the promotion of employability.